The Role of Spillovers in Okun’s law: Empirical Evidence from Spain - Villaverde, José; Maza, Adolfo (Panoeconomicus, 2021)
The Great Recession of the late 2000s has brought to the fore, once again, the relevance of the relationship between output performance and labour market developments all over the world. This paper analyses the validity of Okun’s law in Spain by using regional data from 2000 to 2014, which roughly encompasses a complete business cycle. By estimating a Spatial Panel Durbin Model, the results not only show that a robust, inverse relationship between unemployment and output holds for Spain but also the existence of regional spillovers (indirect effects). In addition, they reveal that there are no time asymmetries between the expansion and recession phases of the business cycle and that human capital, the share of the construction sector, and the share of temporary workers are key factors in explaining unemployment changes. From a policy perspective, our findings support the idea of implementing region-specific policies, since indirect effects are less relevant than direct ones. In any case, national policies would also be effective. These policies, whatever their scope, should be mainly supply-side oriented in expansions (largely labour market policies) and demand-side focused in contractions. Keywords: Unemployment, Output, Spanish regions, Spatial econometrics. JEL: R11, R15.